Implicit causality and consequentiality of action verbs - Solstad, Torgrim; Bott, Oliver (Frontiers in Language Sciences, 2023)
Investigating Implicit Causality (I-Caus) and Implicit Consequentiality (I-Cons) biases associated with action verbs (e.g. Peter praised/healed Mary because/and so . . . ), this paper sheds light on the nature of the coreference and coherence biases associated with Implicit Causality verbs. We provide evidence in support of the Two-Mechanism Account (Solstad and Bott, 2022, "On the nature of implicit causality and consequentiality: the case of psychological verbs", Lang. Cogn. Neurosci. 37), according to which I-Caus and I-Cons are driven by two different mechanisms: While I-Caus derives from empty explanatory slots for explanations in verb semantics, I-Cons follows from the general discourse principle of Discourse Contiguity. Evidence is provided by three production experiments in German investigating the coreference and coherence properties of agent-evocator and causative agent-patient verbs (e.g., praise vs. heal), which differ with regard to the availability of explanatory slots for I-Caus. Experiment 1 established I-Caus and I-Cons coreference biases for the two verb classes, while Experiment 2 investigated their corresponding coherence biases, showing that they pattern as predicted on the Two-Mechanism Account. Finally, Experiment 3 provided empirical evidence on the fine-grained types of causal relations associated with I-Caus and I-Cons for the two verb types.